Спеціально створені організації (ССО) - нові учасники будівельно-інвестиційного процесу - Лагутін, Г. В. (Ways to Improve Construction Efficiency, 2012)
The article focused on the processes of creating special organizations (CCO) as new members of construction and investment process, and as an effective mechanism for the construction and modernization investment sector as a whole. The above investment and construction associations are established in Ukraine to accumulate resources investment companies, financial institutions, construction and real estate companies and their future directions for the preparation of large-scale investment and construction projects of industrial and social facilities.